"Aliens" in the United States: A Collaborative Autoethnography of Foreign-Born Faculty. (July 2020) - Cruz, Joelle; McDonald, James; Broadfoot, Kirsten; Chuang, Andy Kai-chun; Ganesh, Shiv
We draw from our lived experiences as foreign workers in the U.S. academy to explore how foreign academic worker identity is constituted in the contemporary United States. We practice intersectionality by considering how our experiences of "foreignness" in the academy are intertwined with other markers of difference, including race, gender, sexuality, national origin, and age. We also draw from tenets of collaborative autoethnography, producing insight on three constitutive features of foreign worker identity through four narratives that draw from different genres in the autoethnographic tradition. The article highlights the value of collaborative autoethnography as a method of inquiry and reflection in organizational studies, provides a rare account of the ways in which intersectionality is negotiated in everyday life by foreign-born academics, and identifies features of the performance of foreign worker identity related to spatiality, presence, and absence.